A new ALBI‐based model to predict survival after transarterial chemoembolization for BCLC stage B hepatocellular carcinoma. (30th July 2019) - Lee, I‐Cheng; Hung, Ya‐Wen; Liu, Chien‐An; Lee, Rheun‐Chuan; Su, Chien‐Wei; Huo, Teh‐Ia; Li, Chung‐Pin; Chao, Yee; Lin, Han‐Chieh; Hou, Ming‐Chih; Huang, Yi‐Hsiang
Abstract: Background & Aims: Transarterial chemoembolization (TACE) is a standard treatment for Barcelona Clinic Liver Cancer (BCLC) stage B hepatocellular carcinoma (HCC), but the outcome varied. This study aimed to develop a model to predict the outcome of TACE in HCC patients. Methods: Consecutive 570 treatment‐naïve BCLC stage B HCC patients undergoing TACE as the initial treatment from 2007 to 2016 were retrospectively enrolled. Factors associated with survival were analysed. Patients undergoing TACE from 2007 to 2011 constituted the training cohort (n = 293), while patients undergoing TACE from 2012 to 2016 constituted the validation cohort (n = 277). Homogeneity and corrected Akaike information criterion (AICc) were compared between each prognostic model. Results: A total of 1796 TACE sessions were performed for the 570 patients during the median follow‐up period of 18.3 months. By multivariate analysis, beyond up‐to‐11 criteria (hazard ratio [HR] = 1.694, P  < .001), alpha‐foetoprotein >200 ng/mL (HR = 1.771, P  < .001) and albumin‐bilirubin (ALBI) grade 2 or 3 (HR = 1.817, P  < .001) were independent predictors of overall survival (OS) in the training cohort. An ALBI‐TAE model based on the three independent predictors of OS from the training cohort was developed to classify HCC patients into four subgroups. The performance of the ALBI‐TAE model was superior to other prognostic models with lowest AICc values and highest homogeneity in both the training and validation datasets as well as the overall cohort. Conclusions: Albumin‐bilirubin grade is an important factor associated with survival in BCLC stage B HCC patients undergoing TACE. ALBI‐TAE model can be applied to select patients who can get most benefit from TACE.